POTENTIAL FOR AGRO-TOURISM DEVELOPMENT IN NGGORANG VILLAGE, KOMODO DISTRICT, MANGGARAI BARAT REGENCY WITH A SYSTEM DYNAMIC APPROACH - Gabriela T. S. Hadia; Yakobus C. W. Siubelan; Marthen Robinson Pellokila; Maximillian M. J. Kapa (Undana Press, 2026)
This research was conducted in Nggorang Village, Komodo District, Manggarai Regency for one month (January-February). The purpose of this study was to determine the influence of Labuan Bajo tourism on agro-tourism development, agro-tourism potential, commodities that can be developed as agro-tourism and agro-tourism development models in Nggorang Village, Komodo District, West Manggarai Regency and the direction of agro-tourism development in Nggorang village with a dynamic system approach. To achieve the research objectives, there are two analytical methods used, namely Multiple Linear Analysis to determine the Effect of Labuan Bajo Tourism on Agrotourism Development in Nggorang Village and Dynamic Systems to determine the Potential for Agro-tourism Development, Commodities that can be developed as Agro-tourism, Agro-tourism Development Models, Directions for Agro-tourism Development in Nggorang village. Based on the results of the study using multiple linear regression analysis, namely the influence of Labuan Bajo tourism, namely the number of tourist objects, tourist visits, and the availability of agricultural commodities in Agrotourism Development in Nggorang Village. Meanwhile, based on the dynamic system analysis, it shows that there are links and interactions between the components of attractions, facilities, infrastructure, transportation, hospitality towards the direction of agro-tourism development in Nggorang Village. From the results of the system analysis of 5 (five) components, it is found that the facilities and transportation components have a very increasing percentage level until 2030. less than 10%, this means that the dynamic system model in this study is valid and acceptable.